Attraction, marital satisfaction of couples younger men-older women relationship. - Nunez, Analiza A.
The present study exmained the attraction, marital satisfaction of couples: younger men - older women relationship. A total of 8 people or couples consisted the sample, a couple from Lapuz and 3 couples from B. Obrero, Iloilo City. The researcher made use of open - ended questioning to explore deeper into the aspects of marital satisfaction; 4 questions on personality traits, financial and economic ability, supportive behavior, complementary of needs, similarly, emotional maturity and stability; and 5 questions for age and sexuality. The questions were in Yes/No pattern for explanations. The 7 - point marital satisfaction scale was used to determine the couple's level of satisfaction. Despite of he differences in age, educational background, religion, respondents claimed that they are happy with their married life. The age differences do not affect sexual life. Couples tend to diminish the shortcomings of each partner as they learn to accept and deal with them.